The effect of emotional intelligence, compensation and work environment on work engagement - Diah Pranitasari; Wati Setianingsih; Dodi Prastuti; Pristina Hermastuti; Enung Siti Saodah (Badan Pengembangan Sumber Daya Manusia Provinsi DKI Jakarta, 2022)
This study aims to determine some factors that influence employee work engagement. The factors examined in this study were emotional intelligence, compensation and work environment. The results of this study are expected to be input for companies in order to enhance employee work engagement. The study was conducted in Gramedia Kelapa Gading Bookstore employees. The research method is a survey. The population in this study were all 100 employees of Gramedia Bookstore Kelapa Gading, using saturated sampling techniques. The data analysis techniques and data processing used are the Structural Equation Modeling (SEM) method and SmartPLS 3.0 consecutively. The results of this study are as follows: (1) the influence of the emotional intelligence on work engagement is 38%; (2) the effect of the compensation on work engagement is 6%; (3) the influence of the work environment on work engagement is 42%; (4) the effect of the emotional intelligence, compensation and work environment on work engagement is 52%; and the remaining 48% is influenced by other factors not examined in this study.